2009
DOI: 10.1210/en.2009-0121
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Estrogen Receptor-Related-α Increases Osteoblastic Differentiation and Cancellous Bone Mineral Density

Abstract: The nuclear orphan receptor human estrogen receptor-related receptor (ERR)-alpha is implicated in bone metabolism. We studied the effect of ERRalpha silencing in human mesenchymal stem cells (hMSCs) during osteoblastogenesis. We found that ERRalpha silencing led to an increase of bone sialoprotein and a decrease of osteopontin mRNA levels, suggesting enhanced osteoblastic differentiation. This was confirmed by an increased ability of hMSCs to deposit calcium. Concomitantly, knockdown of ERRalpha inhibited adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 37 publications
3
49
0
Order By: Relevance
“…ERR␣ target gene in rodent cells (17), SOX9 was dose-dependently down-regulated in OA chondrocytes after 24 hours of XCT790 treatment ( Figure 6A). Interestingly, XCT790 dose-dependently decreased the IL-1␤-induced ERR␣ expression at both the mRNA and protein levels ( Figure 6B), suggesting an autoregulation of ERR␣ in the IL-1␤ pathway.…”
Section: Pka-and Camp-dependent Up-regulation Of Err␣ By Il-1␤mentioning
confidence: 99%
See 1 more Smart Citation
“…ERR␣ target gene in rodent cells (17), SOX9 was dose-dependently down-regulated in OA chondrocytes after 24 hours of XCT790 treatment ( Figure 6A). Interestingly, XCT790 dose-dependently decreased the IL-1␤-induced ERR␣ expression at both the mRNA and protein levels ( Figure 6B), suggesting an autoregulation of ERR␣ in the IL-1␤ pathway.…”
Section: Pka-and Camp-dependent Up-regulation Of Err␣ By Il-1␤mentioning
confidence: 99%
“…ERR␣ regulates fatty acid oxidation and the adaptive bioenergetic response (13,14). ERR␣ is highly expressed in skeletal (bone and cartilage) tissues (15,16) and has been reported to regulate osteoblast development and bone formation both in vitro (15,16) and in vivo (17,18). ERR␣ expression in fetal and adult articular chondrocytes suggests that it may be involved not only in cartilage formation, but also in its maintenance and integrity throughout the lifetime of the tissue.…”
mentioning
confidence: 99%
“…Numerous population genetic studies have provided evidence of an association between ESR1 polymorphisms and osteoporotic risk (Liu et al, 2006). A mutant ESR1 gene has been found to result in reduced BMD in humans (Smith et al, 1994) and mice (Delhon et al, 2009). In addition, the ESR1 gene is also positively correlated with the expression of the IGF1 (insulin-like growth factor 1) gene (Mendez et al, 2006) and Runx2 (Khalid et al, 2008), another important osteogenic growth factor that enhances the function of osteoblasts and prevents osteoblastic apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…(21) In contrast, two separate studies showed increased bone mineral density with deletion of ERRa in mice. (22,23) Speciesspecific responses, ie, differences between rats and mice in which studies were done, may underlie some of the differences. As likely, however, are the diverse contributions of both cellautonomous ERRa functions in OBs and nonautonomous functions (impact of ERRa-expressing adipocytes, mesenchymal …”
Section: Errs In Osteoblastsmentioning
confidence: 99%
“…(21,22,24) Interestingly, some authors suggest that ERRa may play different roles in bone versus adipose tissues under different physiological conditions, depending on which PGC1 family member is regulated. (15,21,22) ERRa expression is dysregulated in OBs in a mouse rheumatoid arthritis model and in chondrocytes in human OA, both conditions more prevalent with aging.…”
Section: Faomentioning
confidence: 99%